Tinjauan Tingkat Kecemasan Atlet Panahan Padang Archery Club - Bayu Saputra Tamba; Endang Sepdanius (Jurnal IKEOR, 2023)
The problem in this study was that when carrying out the exercise to take the total score, mistakes were often made by athletes, especially when carrying out the total score archery exercise per individual, there were problems of anxiety, doubt and when making decisions. This study aims to determine Padang Archery Club archery athlete’s anxiety level during practice during practice Total score 30 meters. The type of research used in this research is descriptive qualitative research. The population in this study amounted to 30 people. Sampling in this study was carried out by purposive sampling, so that the sample was 20 people. The instrument used in this study was the Hamilton Rating Scale For Anxiety questionnaire. Data analysis technique using percentage descriptive analysis. The results of the research on the anxiety level of the Padang Archery Club Archery athletes during a total score of 30 meters exercise, found an average value of 14 or in the mild anxiety category, the maximum value is 25 and the minimum value is 0. Based on the cross results between the exercise score the total score of 30 meters and the level anxiety was found in the exercise category with a total score of 30 meters with a good category, there were 4 samples without anxiety, 1 sample with mild anxiety and 3 samples with moderate anxiety. In the exercise category, a total score of 30 meters was in the moderate category, with 2 samples having no anxiety, 3 samples with mild anxiety and 1 sample with moderate anxiety. The exercise category has a total score of 30 meters with a less category, 1 sample has no anxiety, and 1 sample has mild anxiety. In the exercise category, a total score of 30 meters was very poor, with 3 samples without anxiety and 1 sample with mild anxiety.